PENGARUH PROMOSI, INOVASI, HARGA, TERHADAP PEMBELIAN ULANG DI TOKO OLEH-OLEH HAJI DENGAN LOYALITAS SEBAGAI VARIABEL MEDIASI - Dadang Suhardi (ITB AAS INDONESIA Surakarta, 2021)
This study aims to examine the effect of promotion, innovation, and price on repeat purchase in toko oleh-oleh haji with loyalty as a mediating variabel. The research problem is how to increasing customer loyalty toward repurchase intention in toko oleh-oleh haji. The variable used in this study is promotion, innovation, price as variabel independen, loyalty as variable intervening and repeat purchase as variabel dependen. The sampling method used on this research is purposive sampling technique. Sample collected from 150 respondents of customer in toko oleh-oleh haji. Technique of data collection conducted by survey through interviews and questionnaires. Data analysis was performed by descriptive analysis method and the method of Partial Least Square (PLS). The result showed that customer on average make repurchase in toko oleh-oleh haji more than twice. The result of data anlysis using the PLS indicates that there is a positive and significant through promotion, innovatin, and price in the repeat purchase. Based on the research results, repeat purchase can be increased through consumer loyalty.